PENGARUH PELATIHAN DAN DISIPLIN TERHADAP KINERJA KARYAWAN DENGAN MOTIVASI SEBAGAI VARIABEL MODERATING PADA PT ISS INDONESIA PENEMPATAN AREA INDOSIAR VISUAL MANDIRI - Umariah; Hamzah, Muhammad Ichwan (JEBI | Jurnal Ekonomi Bisnis Indonesia, 2024)
The aim of this research is to determine the effect of training and discipline on employee performance with motivation as a moderating variable. The sample in the study used a simple random sampling technique with a total of 99 respondents. Data was measured using a Likert scale and data analysis used the SmartPLS 3.0 program. The results of this research directly analyze discipline variables that influence employee performance and motivation, training variables influence motivation and have no influence on employee performance and motivation variables influence employee performance. The results of the analysis indirectly influence discipline and training variables on employee performance which is mediated by motivation. Several recommendations for research are presented based on the conclusions and suggestions regarding the results of this research